Application of cinnamon and gotu kola supplements for increasing quail hematological status (Coturnixcoturnix-australica). (May 2019) - Mas'adah, S M; Sunarno,; Djaelani, M A
Abstract: Cinnamon and gotu kola are herbal plants that are rich in polyphenol-type antioxidants. This type of antioxidant has been known to have an important role in stimulating an increase in biological function, especially hematological status. Quail with increased haematological status can be known from hemoglobin levels and erythrocyte counts per mm3 of blood. The aim of this study was to analyze the hematological status of quail Australian strains by adding cinnamon and gotu kola leaves supplements with variable hemoglobin levels, erythrocyte levels, and body weight supporting variables. The study design used a Completely Randomized Design consisting of 8 treatments with 3 replications. The treatment given includes control, feed supplemented with cinnamon bark powder 5% or 10%, supplementation of gotu kola leaf flour 5% or 10%, combination of cinnamon powder flour supplement with gotu kola (5%: 5%, 5%: 10 % or 10%: 5%). The results of the study were analyzed by Analysis of Variance (ANOVA) which continued with Duncan's Test at a significance level of 5%. The results showed that the supplement of cinnamon bark and gotu kola leaves in feed gave a significant effect on body weight, hemoglobin levels, and the number of erythrocytes (P <0.05). A combination of gotu kola cinnamon-bark supplement with a ratio of 5%: 10% gives an effect on increasing hemoglobin and erythrocyte levels with a higher value than other treatments, which is equal to 13 g / % and 2, 588, 000 per mm3. Quail body weight in each treatment was not significantly different. The conclusion of this study is the addition of combination combinations of gotu kola cinnamon flour with a ratio of 5%: 10% can improve the hematological status of quails, so that the composition of this combination of ingredients can be used to increase the productivity of Australian strains quail laying.